EFEKTIVITAS KONSELING RASIONAL EMOTIF BEHAVIORAL DALAM MENINGKATKAN SELF-REGULATED LEARNING SISWA SEKOLAH MENENGAH KEJURUAN - Yuningdartie, Yuningdartie (Jurnal Bimbingan dan Konseling Borneo, 2022)
This study is motivated by learning difficulties and low learning achievement experienced by students because students do not have the ability to self-regulate in learning. To have self-regulation in learning, students need Self-Regulated Learning. This study aims to test the effectiveness of Behavioral Rational Counseling in improving students' Self-Regulated Learning. This study used a quantitative- qualitative approach (mixed methods) and a quasi-experimental research design using the Nonequivalent (Pre-Test and Post-Test) Control-Group Design. This research was conducted with student research subjects selected purposively. The research instrument used was the Self-Regulated Learning questionnaire instrument. The research was carried out in four steps: 1). preliminary study, 2). preparation of intervention programs, 3). rational validation of intervention programs, and 4). effectiveness test of intervention programs. The results of the preliminary study showed that the average student's Self-Regulated Learning was in the medium category, meaning that students often used Self- Regulated Learning skills. The results of the intervention program effectiveness test showed that the Rational Emotive Behavioral Counseling intervention program was proven to be effective in improving the Self-Regulated Learning of Vocational High School students..Keywords: Effectiveness, Self-Regulated Learning, Rational Emotive Behavioral Counseling